Farmers’ Response to the Integrated Pest Management Program in Murtigading Village, Bantul, Indonesia - Rozaki Zuhud; Pangesthi Hayuningrat Ilham; Moses Tjale Malose; Aula Ardila Riska (E3S Web of Conferences)
The number of longan plants shows an increase, this is because many farmers see its potential. This condition requires an integrated pest control program in Murtigading Village. This study aims to determine the farmers’ response toward integrated pest management program. The method used in this study is scoring, and Spearman Rank for the relationship between variables. The results showed that the category knowledge knew, the category attitude was quite happy, and the actions were done quite a lot by longan farmers. The factors that correlate is quite significant, namely land area with cognitive attitudes, income with cognitive attitudes and income with actions. Meanwhile, the factors that are low correlated are the age factor with cognitive attitudes and affective attitudes, education with cognitive attitudes, land area with affective attitudes and actions, income with affective attitudes. Factors that correlate very low are age with affective attitudes, education with affective attitudes and actions.